ECONOMIC EFFICIENCY OF MILK PRODUCTION IN AGRICULTURAL ENTERPRISES - Величко, Є. І. (Scientific Progress & Innovations, 2015)
Economic efficiency of milk production is considered in agricultural enterprises. We investigated economic efficiency of milk production on the example of «Agricultural Firm named after T. G. Shevchenko» Vovchansk district of Kharkiv region. The basic statistical indexes of effectiveness of activity of the probed economy were used for this purpose. As a result of study and generalizations of experimental data of research are grounded that «Agricultural Firm named after T. G. Shevchenko» is an effective agricultural enterprise. The basic ways of increase of profitability of suckling stock-raising of enterprise are certain.